MAXIMUM RIDE : THE ANGEL EXPERIMENT - Patterson, James; James Patterson (United States Little, Brown, 2005)
Maximum Ride: The Angel Experiment, the first novel in James Patterson's series, follows 14-year-old Max and her "flock"$1 (BFang, Iggy, Nudge, the Gasman, and Angel$1 (Bwho are 98% human and 2% avian, possessing wings and special abilities. After escaping "The School" where they were raised in cages, the flock is hunted by Erasers, wolf-human hybrids. The plot hinges on rescuing the youngest member, Angel, who is recaptured and taken back to the lab.s
English
Keywords: Young adult fiction; science fiction